Effects of 3-month CPAP therapy on brain structure in obstructive sleep apnea: A diffusion tensor imaging study - Liu, Xiang; Wei, Zhipeng; Chen, Liting; Duan, Wenfeng; Li, Haijun; Kong, Linghong; Shu, Yongqiang; Li, Panmei; Li, Kunyao; Xie, Wei; Zeng, Yaping; Huang, Ling; et al. (Frontiers in Neurology, 2022)
White matter (WM) fiber integrity in patients with obstructive sleep apnea (OSA) is associated with cognitive impairment, which can be alleviated by continuous positive airway pressure (CPAP). In this study, we aimed to investigate the changes in WM in patients with OSA at baseline (pre-CPAP) and 3 months after CPAP adherence treatment (post-CPAP), and to provide a basis for understanding the reversible changes after WM injury in this disease.Magnetic resonance imaging was performed on 49 severely untreated patients with OSA and 46 good sleepers. Tract-based spatial statistics was used to evaluate the fractional anisotropy, mean diffusion coefficient, axial diffusion coefficient (AD), and radial diffusion coefficient of WM. To assess the efficacy of treatment, 20 patients with pre-CPAP OSA underwent magnetic resonance imaging again 3 months later. A correlation analysis was conducted to evaluate the relationship between WM injury and clinical evaluation. Fractional anisotropy and AD in the anterior thalamic radiation, corticospinal tract, forceps major, inferior fronto-occipital tract, inferior longitudinal fasciculus, and uncinate fasciculus were significantly reduced in patients with OSA compared with the good sleepers, and AD in the superior longitudinal fasciculus and cingulate gyrus was significantly reduced (P < 0.05). No significant change in WM in patients with post-CPAP OSA compared with those with pre-CPAP OSA. Abnormal changes in WM in untreated patients with OSA were associated with oxygen saturation, Montreal cognitive score, and the Epworth sleepiness scale.WM fiber integrity was extensively damaged in patients with severe OSA and was related to oxygen saturation and cognitive function. Meanwhile, cognitive recovery was not accompanied by reversible changes in WM microstructure after short-term CPAP therapy.